Diversity of The Ornate Lorikeet (Trichoglossus ornatus) Birds Based on Mitochondrial DNA Protein Coding Gene - Dwi Astuti; Siti Nuramaliati Prijono (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2018)
Ornate lorikeet (Trichoglossus ornatus) is an endemic bird in Sulawesi. Endemism is one of the factors in declining bird’s population. In the case of the birds conservation programme, information about gene diversity is important for basic strategy. Mitochondrial DNA of animals consists of protein coding genes including ND2 gene. This study informs diversity of the Ornate Lorikeet (Trichoglossus ornatus) birds based on DNA sequences of ND2 gene. DNA total was extracted from blood samples of 21 birds. PCR (Polymerase Chain Reaction) was performed and successfully amplified a single DNA fragment of ND2 gene for all birds. DNA fragments were sequenced and totally 997 base pairs were analyzed. NJ tree was constructed using MEGA5. All DNA sequence data showed that between the birds there were 20 polymorphic (segregating) sites with mean genetic distance was 0.004 ± 0.002 (ranged from 0,000 – 0,008), and had 17 sequence haplotypes (HTor1- HTo17). Haplotype diversity (Hd) was 0.967 ± 0.30387 and nucleotide diversity (Pi) was 0.00439 ± 0.0012. Genetic diversity information could be potential relevance to the breeding management for conservation of the birds.